Memoir of light and dust: (Things that enable one to see and things that one actually sees) - Bajracharya, Saroj (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
This write up aims to understand the relationship between the ancient and the modern art in relation to the foundation of the unbound state of mind that has been flowing from primitive time in Nepal. State of mind is generally defined as the mental state or mood of a person at a particular time. But in this context, time is an extended and stretched playground for artists where they have sometimes connected and at times disconnected from their primitive native continuity of individual aesthetics and collective social beliefs. And this connection and disconnection from what appears as the ancient state of mind is rather the elementary characteristics of our society that has merged with western propagated modernity in terms of arts as well as science; we have local modern art façade which got fueled around the mid 19th century in Nepal and combusted in the mid 20th century here. When one enters into this creative façade, one can still feel the unbound state of mind that emanates mystic, relaxed and harmonious qualities in some of the artworks by local artists. When these qualities unify with popular styles of expressions in Nepal, we coincide with the Nepaliness in a work of art of recent times.